2019
DOI: 10.1002/asia.201801710
|View full text |Cite
|
Sign up to set email alerts
|

NixCo3‐xO4 Nanoneedle Arrays Grown on Ni Foam as an Efficient Bifunctional Electrocatalyst for Full Water Splitting

Abstract: Developing highly active, stable and robust electrocatalysts based on earth-abundant elements for oxygen evolution reaction( OER) and hydrogen evolution reaction (HER) is important for many renewable energy conversion processes. Herein, Ni x Co 3-x O 4 nanoneedle arrays growno n3D porous nickel foam (NF) was synthesized as ab ifunctional electrocatalyst with OER and HER activity for full water splitting. Benefiting from the advantageous structure, thec omposite exhibits superior OER activity with an overpotent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 49 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…[29] Moreover, the oxide compounds combining nickel and cobalt (for instance, NiCo 2 O 4 ) as OER catalysts have also attracted increasing interests. [30][31][32][33][34] Fang et al showed that both the (111) and (110) facets in NiCo 2 O 4 nanosheets exhibited high OER activity. [30] Bao et al reported that mesoporous Ni x Co 3-x O 4 nanoneedle arrays exhibited a large electrochemically active area and showed a promising OER activity (320 mV at 10 mA cm −2 , Tafel slope of 38 mV dec −1 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[29] Moreover, the oxide compounds combining nickel and cobalt (for instance, NiCo 2 O 4 ) as OER catalysts have also attracted increasing interests. [30][31][32][33][34] Fang et al showed that both the (111) and (110) facets in NiCo 2 O 4 nanosheets exhibited high OER activity. [30] Bao et al reported that mesoporous Ni x Co 3-x O 4 nanoneedle arrays exhibited a large electrochemically active area and showed a promising OER activity (320 mV at 10 mA cm −2 , Tafel slope of 38 mV dec −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…[30] Bao et al reported that mesoporous Ni x Co 3-x O 4 nanoneedle arrays exhibited a large electrochemically active area and showed a promising OER activity (320 mV at 10 mA cm −2 , Tafel slope of 38 mV dec −1 ). [31] However, it is not straightforward to compare the OER performance of NiO, Co 3 O 4 , and NiCo 2 O 4 reported in literatures since these materials were synthesized by a large variety of methods and exhibited quite different surface morphologies and structural features. It is known that the OER activity of electrocatalysts depends on not only the material composition but also their surface morphology, micro-/nano-structural features, facets, synthesis methods and so on.…”
Section: Introductionmentioning
confidence: 99%
“…With the continually increasing crisis of energy crisis and environment pollution, renewable and clean energy sources have been widely concerned in recent years. Hydrogen, which can be produced from splitting of water, has been regarded as one of the most promising candidates for replacing fossil fuels in the future . Electrocatalytic water splitting is a sustainable and efficient approach for large‐scale hydrogen production .…”
Section: Introductionmentioning
confidence: 99%
“…; Table S2: Comparison of the OER performances of Ag NWs@Ni 0.33 Co 0.67 P with the previously reported electrocatalysts at alkaline media; Table S3: Comparison of the HER performances of Ag NWs@Ni 0.33 Co 0.67 P with the previously reported electrocatalysts at alkaline media; Table S4: Comparison of overall water splitting performances of Ag NWs@Ni 0.33 Co 0.67 P with the previously reported electrocatalysts at alkaline media. References [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ] are cited in the Supplementary Materials.…”
mentioning
confidence: 99%